2020
DOI: 10.1371/journal.pntd.0008138
|View full text |Cite
|
Sign up to set email alerts
|

Altered composition and functional profile of high-density lipoprotein in leprosy patients

Abstract: The changes in host lipid metabolism during leprosy have been correlated to fatty acid alterations in serum and with high-density lipoprotein (HDL) dysfunctionality. This is most evident in multibacillary leprosy patients (Mb), who present an accumulation of host lipids in Schwann cells and macrophages. This accumulation in host peripheral tissues should be withdrawn by HDL, but it is unclear why this lipoprotein from Mb patients loses this function. To investigate HDL metabolism changes during the course of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…The role and functionality of ApoA1 in leprosy thus remains to be further elucidated. The influence of ApoA1 on lipid metabolism is of interest as dysfunctional high-density lipoprotein (involved in cholesterol transport to the liver of which the main protein is ApoA1) related to altered ApoA1 levels has been observed in MB patients ( 34 ). Moreover, it was suggested that M. leprae can directly affect ApoA1 biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The role and functionality of ApoA1 in leprosy thus remains to be further elucidated. The influence of ApoA1 on lipid metabolism is of interest as dysfunctional high-density lipoprotein (involved in cholesterol transport to the liver of which the main protein is ApoA1) related to altered ApoA1 levels has been observed in MB patients ( 34 ). Moreover, it was suggested that M. leprae can directly affect ApoA1 biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…HDL has been found to contain a diverse set of enzymatically active proteins, hydroxylated derivatives of polyunsaturated fatty acids, and hydroperoxides, and although HDL is regarded as anti-oxidative and antiinflammatory, during the acute phase reaction, oxidative and inflammatory reactions take over (Lemes et al, 2020;Navab et al, 2001;Vaisar et al, 2007). Our finding that PLY-modified HDL contains a high concentration of MDA suggests dysfunction of the particle and enhancement of oxidative reactions (Shao et al, 2010).…”
Section: Ll Open Access Isciencementioning
confidence: 68%
“…The result of the studies has been sum up in Table 1. Among the 15 studies, we summarize that the main topics discussed related to lipid and leprosy include: (1) Serum lipid profile alterations in leprosy in six studies [20], [21], [22], [25], [27], [28] (2); lipid metabolism in leprosy and role of their metabolites [23], [24], [32];…”
Section: Resultsmentioning
confidence: 99%